Developing and testing innovative beam–column joint damper. (July 2022) - Zhao, Xin; Qi, Ai
Abstract: This paper proposes a new type of metal damper, or rather a slotted beam–column joint damper (SJD), suitable for beam–column energy-dissipating joints of fabricated structures to reduce damage to main structures in earthquakes. An SJD comprises variable-thickness flanges and a slotted web. The flanges are the primary energy-consuming part, and the web ensures the necessary bearing capacity. The characteristics of the artificial plastic hinge frame were analyzed, and the effects of the thickness of the flanges and the web slotting on the weakening and plasticity ratios were discussed. Four slotted beam–column joint dampers with distinct material properties or slotting directions were designed and constructed for the quasi-static cyclic loading tests. The results confirmed that the SJD had good hysteretic characteristics, ductility, and stable energy dissipation. However, as discussed in detail, the slotted beam–column joint dampers with various material properties and slotting directions differed in yield characteristics, failure modes, and energy dissipation. This study also discussed the detachable connection for this new damper.